2006
DOI: 10.1523/jneurosci.0990-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Polyglutamine Proteins at the Pathogenic Threshold Display Neuron-Specific Aggregation in a Pan-NeuronalCaenorhabditis elegansModel

Abstract: The basis of neuron-specific pathogenesis, resulting from the expression of misfolded proteins, is poorly understood and of central importance to an understanding of the cell-type specificity of neurodegenerative disease. In this study, we developed a new model for neuron-specific polyQ pathogenesis in Caenorhabditis elegans by pan-neuronal expression that exhibits polyQ length-dependent aggregation, neurotoxicity, and a pathogenic threshold at a length of 35-40 glutamines. Analysis of specific neurons in C. e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
214
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(232 citation statements)
references
References 50 publications
9
214
0
Order By: Relevance
“…Whether this form of pathological behavior uses molecular mechanisms common to higher animals remains to be determined. A similar approach has recently revealed polyglutamine threshold toxicity in a transgenic C. elegans model of Huntington's disease (Brignull et al, 2006). (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Whether this form of pathological behavior uses molecular mechanisms common to higher animals remains to be determined. A similar approach has recently revealed polyglutamine threshold toxicity in a transgenic C. elegans model of Huntington's disease (Brignull et al, 2006). (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…These advantages, together with genome-wide tools for genetic screens and a short life cycle and life span, also allow rapid testing of hypotheses. Observations from many laboratories have shown that polyQ or A␤ proteins are toxic in multiple cells and tissues of Drosophila and C. elegans including retinal neurons, chemosensory, mechanosensory, motor neurons, and body wall muscle cells (Link 1995;Warrick et al 1998;Faber et al 1999;Marsh et al 2000;Parker et al 2001;Morley et al 2002;Takeyama et al 2002;Brignull et al 2006). While no single model recapitulates all features of a disease it is evident that each system has contributed unique insights that have validated the general approach.…”
Section: Insights On Neurodegenerative Disease and Protein Conformatimentioning
confidence: 99%
“…Worms were imaged using an Axioimager (Zeiss) or an Ultraview Vox spinning disc confocal (Perkin Elmer) microscope and analyzed with either Axiovision 4.7 (Zeiss) or Volocity 5 (Perkin Elmer) software. Fluorescence recovery after photobleaching (FRAP) analysis was performed as previously described (Brignull et al 2006).…”
Section: Rnaimentioning
confidence: 99%
“…This might be due to the lower copy number of our SRP-2 transgenes, which were integrated by biolistic transformation avoiding excessive overexpression (Praitis et al 2001). To further define the nature of SRP-2 aggregates, we performed FRAP experiments for SRP-2 H302R , YFP, and polyQ-YFP expressed in body wall muscle cells (Morley et al 2002;Brignull et al 2006). In contrast to the wild-type protein, no obvious recovery was detectable for the mutant form ( Figure 3, B and C), indicating that SRP-2 H302R forms insoluble polymers within cellular compartments.…”
Section: Analysis Of Srp-2 Aggregation In C Elegansmentioning
confidence: 99%